What's wrong with bilingualism and becoming multilingual? An analysis of discourses in Alberta's updated French policy - Gillis, Steven (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2025)
This paper employs the 'What's the problem represented to be?' (WPR) method to explore language learning and language planning policy in Alberta, Canada through the provincial government's newly published update of a document titled 'French Policy'. Through an analysis of its discourse, along with the political and pedagogical contexts in which the French Policy finds itself, the underlying belief emerges that learning in languages other than English in Alberta should only be reserved to the few who qualify for official minority education obligated by the Canadian Charter of Rights and Freedoms. The argument is made in this paper that the province would actually benefit from the opposite: that an educational turn towards promoting the learning of multiple languages would better achieve the goals of inclusion and social and economic progress for which the government is claiming to be endeavouring in the French Policy and elsewhere.